Megacystis-microcolon-intestinal hypoperistalsis syndrome. Issue 2 (February 1984) - Vinograd, I; Mogle, P; Lernau, O Z; Nissan, S
Abstract : Two neonates with megacystis-microcolon-intestinal hypoperistalsis syndrome are described. Both were boys. The main manifestation was functional obstruction of the urinary and gastrointestinal tracts. While there is no explanation as yet for the aetiology and pathogenesis, the diagnosis is simple, the treatment symptomatic, and the outcome fatal.